In Situ Atomic Force Microscopy Studies of the Effect of Indolicidin on E.coli Cells - Fojan, Peter (Journal of Self Assembly and Molecular Electronics, 2023)
E.coli cells were succesfully attached to both gelatin coated surfaces and polylactic acid honeycomb patterned mica surfaces as determined by in situ atomic force microscopy. The gelatin coated surfaces provided a softer support onto which the E.coli cells were capable of slightly submerging leading to a better adhesion compared to the harder surfaces consisting of polylactic acid polymer surfaces. After continuous scanning in liquid media, the E.coli cells remained rod shaped and smooth. Indolicidin, a 13-AA linear antimicrobial peptide, was injected in order to visualize the peptide-membrane interac- tions in real time. Instantly after the injection of the peptides, the bacterial membranes were observed to be distorted and seemed to melt proceeding as a function of time. In conclusion, these experiments proved that the E.coli cells were not ruptured as could be expected due to pore formation and disruption of the osmotic pressure. This indicates a possible intracellular target killing mechanism of indolicidin interacting with E.coli cells.